Functional State of the Motor Centers of the Lumbar Spine after Contusion (Th8-Th9) with Application of Methylprednisolone-Copolymer at the Site of Injury - Maxim Baltin; Victoriya Smirnova; Regina Khamatnurova; Diana Sabirova; Bulat Samigullin; Oskar Sachenkov; Tatyana Baltina (Biomedicines, 2023)
Spinal cord injuries must be treated as soon as possible. Studies of NASCIS protocols have questioned the use of methylprednisolone therapy. This study aimed to evaluate the effect of local delivery of methylprednisolone succinate in combination with a tri-block copolymer in rats with spinal cord injury. The experiments were conducted in accordance with the bioethical guidelines. We evaluated the state of the motor centers below the level of injury by assessing the amplitude of evoked motor responses in the hind limb muscles of rats during epidural stimulation. Kinematic analysis was performed to examine the stepping cycle in each rat. Trajectories of foot movements were plotted to determine the range of limb motion, maximum foot lift height, and lateral deviation of the foot in rats on the 21st day after spinal cord injury. We have shown that the local application of methylprednisolone succinate in combination with block copolymer leads to recovery of center excitability by 21 days after injury. In rats, they recovered weight-supported locomotion, directional control of walking, and balance. The proposed assessment method provides valuable information on gait disturbances following injury and can be utilized to evaluate the quality of therapeutic interventions.